2020
DOI: 10.1111/ijd.15092
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in POFUT1 gene associated with Dowling–Degos disease and hidradenitis suppurativa

Abstract: A previous report showed a 10% complete remission rate after an average follow-up of 3.5 years in 150 patients with pretibial myxedema. 2 According to another study of long-term outcome of pretibial myxedema in 178 patients with pretibial myxedema, a 50% complete remission rate was achieved after 17 years in patients who had gone untreated for cutaneous lesions. 3 In contrast, our patient developed a marked deterioration over a period of 14 years. Mild cases may show spontaneous regression, while severe cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In recent years, mutations of POFUT1, PSENEN, and NCSTN have been successively identified in patients with HS-DDD, strongly suggesting that deficient Notch signaling may be the potential link between these two apparently different conditions. 5 In this study, by whole-exome sequencing, a pathogenic mutation of POFUT1 was identified in the patient with SK-DDD for the first time, which indicates that deficient Notch signaling might also play a crucial role in the co-occurrence of SK and DDD. More cases and further studies are definitely needed to confirm the association between POFUT1 and SK-DDD.…”
Section: Loss-of-function Mutations In Krt5 Poglut1 Pofut1 Andmentioning
confidence: 59%
“…In recent years, mutations of POFUT1, PSENEN, and NCSTN have been successively identified in patients with HS-DDD, strongly suggesting that deficient Notch signaling may be the potential link between these two apparently different conditions. 5 In this study, by whole-exome sequencing, a pathogenic mutation of POFUT1 was identified in the patient with SK-DDD for the first time, which indicates that deficient Notch signaling might also play a crucial role in the co-occurrence of SK and DDD. More cases and further studies are definitely needed to confirm the association between POFUT1 and SK-DDD.…”
Section: Loss-of-function Mutations In Krt5 Poglut1 Pofut1 Andmentioning
confidence: 59%
“…HS is a chronic inflammatory disorder of the hair and follicles typically involving axillae, buttocks, groin, perineal, and inframammary regions [ 8 ]. According to case reports and clinical studies, concurrent DDD with HS has been reported in 53 cases (including our case) as shown in Table 2 [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]: 2 cases of which are follicular DDD variant and 1 case is associated with Galli-Galli disease, a variant of DDD [ 10 , 33 ]. Most cases reported were of female predominance and more than half presented with at least Hurley stage 2.…”
Section: Discussionmentioning
confidence: 84%
“…Almost all had a family history of HS. Recent genetic studies have found that patients with concurrent DDD with HS mostly have mutation in PSENEN , followed by POFUT1 and a case of NCSTN [ 13 , 14 , 25 , 27 , 28 , 31 ]. Few cases reported association with squamous cell carcinoma, keratoacanthoma, and arthritis [ 17 , 19 , 22 , 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, DDD should be considered in the differential diagnosis of patients presenting with 3,5,7,9,10,12,14,17,18,[28][29][30][31][32][33][34][35][36][37][38] 28,31,42 3 66 (64-68) 0 -EIC 11,12 2 54 (49-58) 50 -Fingernail dystrophy 1, 23 2 48 (36-59) 100 -Amelanocytic malignant melanoma 43 1 5 1 0 -Darier disease 44 1 6 2 0 -Eczematous plaques 8 1 9 100 POFTU1 (n = 1) Ichthyosis vulgaris 4 1 2 5 0 -Keratocanthomas*, 33 1 ---Leukoderma 22 1 26 100 -Palmoplantar hyperhydrosis 22 1 26 100 -Palmoplantar keratodema 22 1 26 100 -Pemphigus vulgaris 11 1 5 8 0 -Pilonidal sinus*, 45 1 ---Psoriasis 6 1 53 100 Recurrent medial thigh abscesses 22 1 27 100 -*Age and gender not reported in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, mutations in keratin 5 (KRT5), keratin 14, protein O-fucosyltransferase 1 (POFUT1), and presenilin enhancer protein 2 gene (PSENEN) have been observed in affected patients. 2,[5][6][7][8][9][10] The concurrent presentation of DDD and hidradenitis suppurativa (HS) has been well described, with multiple studies demonstrating underlying genetic mutations involved in similar pathways, suggesting these conditions may be etiologically related. Other dermatologic conditions have been less commonly reported in conjunction with DDD, with unknown etiologic associations.…”
Section: Introductionmentioning
confidence: 99%